Why Pay More? Tax Planning of Married Couples - Thiess Büttner; Katharina Erbe; Veronika Grimm (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
This paper explores whether tax planning by households is consistent with a minimization of the family tax burden or whether and to what extent altruism and concerns about the tax loss of individual household members matter. To this end, we take advantage of a specific feature of the German tax system which allows married couples to decide which of three different payroll tax regimes applies. Using a 10% random sample of the individual income tax files of all German tax payers, we find that a substantial fraction of all couples choose equal treatment of partners although a preferential tax treatment of the high income earner would yield a higher net family income. Our findings indicate that this result can be partly attributed to equity concerns. Tax planning is used not only to lower the overall tax burden but also to reduce the tax burden on the partner with the lower income.
Keywords: H24; H31; J22; 330